Magnetocrystalline two-fold symmetry in CaFe2O4 single crystal. (27th March 2017) - Gandhi, Ashish Chhaganlal; Das, Rajasree; Chou, Fang-Cheng; Lin, Jauyn Grace
Abstract: Understanding of magnetocrystalline anisotropy in CaFe2 O4 is a matter of importance for its future applications. A high quality single crystal CaFe2 O4 sample is studied by using synchrotron x-ray diffraction, a magnetometer and the electron spin resonance (ESR) technique. A broad feature of the susceptibility curve around room temperature is observed, indicating the development of 1D spin interactions above the on-set of antiferromagnetic transition. The angular dependency of ESR reveals an in-plane two-fold symmetry, suggesting a strong correlation between the room temperature spin structure and magnetocrystalline anisotropy. This finding opens an opportunity for the device utilizing the anisotropy field of CaFe2 O4 .